The TPACK Method Workshop as a 21st Century Learning Innovation for Teachers at SMP N 2 Gadingrejo - Budi Usmantor; Novi Ayu Kristiana Dewi; Yeasy Agustina Sari; Mufid Masngudi (CV. Creative Tugu Pena, 2025)
The article aimed to train teachers at SMP Negeri 2 Gadingrejo in implementing the Technological Pedagogical Content Knowledge (TPACK) framework in classroom learning. Rapid technological advancements require teachers to continuously update their technological competencies to effectively support teaching and learning processes. The quality of learning is determined not only by teachers’ mastery of subject matter and pedagogical skills but also by their ability to integrate technology meaningfully into instruction. Moreover, the use of educational technology contributes to the development of students’ digital literacy and critical thinking skills. The training introduced two technological tools: Google Classroom as a web-based digital learning platform and Adobe Animate as software for developing engaging and interactive learning media. The results indicated that all participating teachers were able to utilize Google Classroom effectively as a digital learning platform. However, additional training is required for Adobe Animate, as many participants experienced difficulties, particularly in understanding ActionScript. This article contributes to strengthening teachers’ TPACK competencies by providing practical training in digital learning platforms and interactive media development, thereby supporting innovative learning practices aligned with 21st-century education demands.